Association of Genetic Variants With Migraine Subclassified by Clinical Symptoms in Adult Females - Kossowsky, Joe; Schuler, Megan S.; Giulianini, Franco; Berde, Charles B.; Reis, Ben; Ridker, Paul M; Buring, Julie E.; Kurth, Tobias; Chasman, Daniel I. (Frontiers in Neurology, 2021)
Migraine is heritable and formally diagnosed by structured criteria that require presence of some but not all possible migraine symptoms which include aura, several distinct manifestations of pain, nausea/vomiting, and sensitivity to light or sound. The most recent genome-wide genetic association study (GWAS) for migraine identified 38 loci. We investigated whether 46 single-nucleotide polymorphisms (SNPs), i.e., genetic variants, at these loci may have especially pronounced, i.e., selective, association with migraine presenting with individual symptoms compared to absence of migraine. Selective genetic associations of SNPs were evaluated through a likelihood framework in the Women's Genome Health Study (WGHS), a population-based cohort of middle-aged women including 3,003 experiencing migraine and 18,108 not experiencing migraine, all with genetic information. SNPs at 12 loci displayed significant selective association for migraine subclassified by specific symptoms, among which six selective associations are novel. Symptoms showing selective association include aura, nausea/vomiting, photophobia, and phonophobia. The selective associations were consistent whether the women met all formal criteria for diagnostic for migraine or lacked one of the diagnostic criteria, formally termed probable migraine. Subsequently, we performed latent class analysis of migraine diagnostic symptoms among 69,861 women experiencing migraine from the WGHS recruitment sample to assess whether there were clusters of specific symptoms that might also have a genetic basis. However, no globally robust latent migraine substructures of diagnostic symptoms were observed nor were there selective genetic associations with specific combinations of symptoms revealed among weakly supported latent classes. The findings extend previously reported selective genetic associations with migraine diagnostic symptoms while supporting models for shared genetic susceptibility across all qualifying migraine at many loci.